Factors Influencing E-Wallet Service on Generation Z in Jakarta, Indonesia - Rabiah, Arbi Siti; Sugianto, Dennis (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
The development of the digital era has affected many aspects of lifestyle, including consumer behavior in financial transactions. The emergence of mobile payment technology, such as E-wallet services, makes it easier for consumers to make transactions digitally without using cash. This study aims to analyze the factors affecting such as perceived ease of use, perceived usefulness, and security on intention to use E-wallet services among Generation Z in Jakarta, Indonesia, with customer trust as a mediating variable. This study uses probability sampling with simple random sampling with respondents 400 Generation Z respondents in Jakarta, Indonesia. The analysis method uses SEM-PLS, consisting of outer and inner models. The results of this study indicate that the variables of perceived ease of use, perceived usefulness, and security are positively significant in the intention to use the variable either directly or through the customer trust variable as an intervening variable. This study concludes that these factors influence the intention to use e-wallet services among Generation Z consumers in Jakarta, Indonesia.